Prognostic value of pre- and post-treatment health-related quality of life in predicting survival of patients with brain metastases. (April 2017) - Wong, Erin; Rowbottom, Leigha; Tsao, May; Zhang, Liying; McDonald, Rachel; Danjoux, Cyril; Barnes, Elizabeth; Chan, Stephanie; Chow, Edward
Aim: The present study aimed to determine the prognostic survival value of pretreatment health-related quality of life (HRQOL) and changes in HRQOL following whole-brain radiation treatment in patients with brain metastases.Methods: Patients who were treated with whole-brain radiation treatment and completed HRQOL questionnaires were included. Univariate and multivariate Cox proportional hazard models of overall survival (OS) were conducted for overall HRQOL and domain scores.Results & conclusion: Patients with lower HRQOL at baseline, especially lower physical functioning and motor dysfunction domains, were more likely to have poorer survival. Changes in overall HRQOL and its domains were not significantly related to OS. Pretreatment HRQOL, especially physical functioning and motor dysfunction, has added prognostic value in patients with brain metastases.